Effects of sterilization techniques on the Pegylated poly (y-benzyl-L-glutamate) (PBLG) nanoparticles (2009)
ABSTRACT: Nanoparticles were prepared by nanoprecipitation technique using poly (1-benzyl-L-glutamate) (PBLG) derivatives. Injectable nanoparticles were assessed for their in vitro properties such as particle size, polydispersity index, zeta potential and surface properties. The possibilities of sterilizing PBLG nanoparticle suspensions by membrane fıltration or autoclaving were evaluated. It was found that among these techniques, sterilization with membrane filtration seemed to be the most appropriate technique with any significant effect on in vitro and surface properties. Sterility was assessed on üe final product according to pharmacopoeial requirements. Sterility testing results showed no microbial contamination indicating that sterile nanoparticle formulations have been achieved after membrane filtration.